2007
DOI: 10.1002/icd.502
|View full text |Cite
|
Sign up to set email alerts
|

Measuring change: current trends and future directions in microgenetic research

Abstract: This special issue is dedicated to research that adopts the microgenetic method in order to investigates change as it is happening. In this commentary we reflect on the diversity of the articles included in this special issue, and examine how the findings from these articles relate to five critical features of change: path, rate, breadth, variability and source. The overarching theme from these findings is that the tidy results reported in cross-sectional studies are not in fact as tidy as they originally appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 46 publications
1
19
0
3
Order By: Relevance
“…Examining the transmission of behaviour and information across groups appears to be ripe for further exploration, as has been highlighted by Flynn & Siegler (2007). The next step appears to be an examination of young children's cultural transmission using open diffusion designs, in which a trained model and a task are introduced to a group of participants at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…Examining the transmission of behaviour and information across groups appears to be ripe for further exploration, as has been highlighted by Flynn & Siegler (2007). The next step appears to be an examination of young children's cultural transmission using open diffusion designs, in which a trained model and a task are introduced to a group of participants at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, changes in reasoning can become visible closely to the moment they happen, thus enabling the discovery of natural developmental and learning trajectories. These trajectories may be considered natural if the practice sessions include no explicit forms of training, such as the provision of elaborate instructions or prompting (Flynn & Siegler, 2007;Siegler, 2006;Siegler & Crowley, 1991). In the present study we investigated whether problem solving trajectories involving analogy tasks showed differing pathways when these were acquired through more 'natural' unprompted opportunities than when a short training procedure is included.…”
Section: Introductionmentioning
confidence: 99%
“…(49,50) using frequent observations over an extended period of time in a small number of cases. These designs have the advantage of being immediately applicable to clinical practice by showing the process of change (as in the case of the daily ups and downs in this study) within and across cases, (51,52,53) although because of small sample size, they cannot prove that a method is effective for the population in general.…”
Section: Subjectsmentioning
confidence: 99%